82 Utility of Ceramide Testing in Men with Erectile Dysfunction. Issue 1 (1st April 2022) - Alom, M; Yang, D; Collins, S; Ziegelmann, M; Helo, S; Kopecky, S; Kohler, T
ABSTRACT: Introduction: Erectile dysfunction (ED) is a known precursor and sequelae to diagnosed cardiovascular disease (CVD). ED AUA guidelines recommend evaluating standard CV risk factors including serum lipids and penile doppler to help stratify CV risk, but few patients are referred for further evaluation. Plasma ceramides are metabolic byproducts that are novel predictors of adverse cardiovascular events resulting from unstable atherosclerotic plaque. CVD risk conferred by ceramide levels has been shown to be independent of conventional risk factors such as LDL and hsCRP levels. Thus, Plasma MI-Heart Ceramide is a new test that useful for evaluating shorter term major adverse cardiovascular events (MACE) in the next 1 to 5 years. Objective: We sought to evaluate the utility of ceramide levels in ED patients Methods: We initiated ceramide testing in all patients with ED in late 2019 (in addition to lipids and Hgba1c). We queried our electronic medical record for ceramide levels and men with a diagnosis of ED. Ceramide levels stratified patients in normal, moderate, high, and very high risk. Twenty eight patients additionally had penile duplex ultrasound (DUS). Left and right peak systolic velocity values were averaged and a value of <25 cm/s was defined as penile arterial insufficiency. Results: 245 men with ED and ceramide levels were analyzed. 44% (n=107) were normal, 42% (n=103) were moderate risk, 12% (n=29) were high risk and 2% (n=6) were very high risk. As result of their ceramide and office evaluation, 42% (15/35) of high/very high risk patients were referred for cardiac evaluation. Comparing ceramide scores in men with penile arterial insufficiency (16.7 cm/sec) vs patients without (43.2 cm/sec), we found no significant difference (p=1). Similarly, when comparing DUS results between ceramide risk categories, we found no significant differences (p=1). Conclusions: One in 7 men presenting to an ED clinic had a high or very high ceramide risk. DUS results did not correlate with ceramide risk. Patients undergoing DUS (even without arterial insufficiency) may benefit from additional ceramide testing and possible cardiac referral. Further study is warranted to optimize utility of ceramide in men with ED and potentially decrease peri-procedural IPP cardiac morbidity. Disclosure: No